Questions Regarding the Implementation of EU Mutagenesis Ruling in France - Bartsch, Detlef; Ehlers, Ulrich; Hartung, Frank; Kahrmann, Jens; Leggewie, Georg; Sprink, Thorben; Wilhelm, Ralf (Frontiers in Plant Science, 2020)
The European Commission has asked EU Member States for comments on a French law notification demanding plant varieties produced with the help of in vitro mutagenesis have to be eliminated from the national catalog of approved varieties because of missing legal authorization deemed required by genetic engineering law. Primary target are herbicide-tolerant Clearfield oilseed rape varieties. The scientific reasoning is questionable, traceability is illusive, and law enforcement is likely to be impossible.